Drawing for interior design - Plunkett, Drew. (London : Laurence King Publishers, 2009)
This volume covers all stages of visual presentation in interior design, from early concept sketches and more evolved technical drawings to complex computer renderings, models for client presentation, and production drawings for contractors. Step-by-step sequences and special tips show students how to make the most of the available media, while practical advice on everything from communicating with clients and contractors to the legal implications of production drawings are covered. A comprehensive and varied selection of drawings from practitioners and student designers will whet readers' appetites, encourage enthusiasm, and suggest possibilities. This book will be an invaluable, inspirational, and practical resource for interior design and interior architecture students and practicing interior designers alike.
Keywords: Interior architecture